2007
DOI: 10.1111/j.1365-246x.2007.03409.x
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic inversion using ℓ1-norm regularization of wavelet coefficients

Abstract: S U M M A R YWe propose the use of 1 regularization in a wavelet basis for the solution of linearized seismic tomography problems Am = d, allowing for the possibility of sharp discontinuities superimposed on a smoothly varying background. An iterative method is used to find a sparse solution m that contains no more fine-scale structure than is necessary to fit the data d to within its assigned errors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
126
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 26 publications
0
126
0
Order By: Relevance
“…There are also variety of works on Xray CT based on discrete transformations or dictionary bases [8], [15], [16]. In this paper, the Dual Tree-Complex Wavelet Transformation (DT-CWT) [17] is used.…”
Section: The Hierarchical Bayesian Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also variety of works on Xray CT based on discrete transformations or dictionary bases [8], [15], [16]. In this paper, the Dual Tree-Complex Wavelet Transformation (DT-CWT) [17] is used.…”
Section: The Hierarchical Bayesian Methodsmentioning
confidence: 99%
“…Many methods have been studied in order to solve this l 1 norm optimization problem, for example the Newton's method [7] and the Split Bregman method [6]. Another class of the regularization method, called "Synthesis", considers a linear sparse transformation f = Dz and minimizes a criterion: J (z) = g − HDz 2 2 + λR(z) for example R(z) = z 1 [8]. When z obtained the object is reconstructed by f = D z.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic tomography, which estimates subsurface geologic facies, also has exploited sparsity for reconstruction. This has been demonstrated with wavelet representations of the subsurface and nonlinear forward models (Loris et al, 2007;Simons et al, 2011). Gholami and Siahkoohi (2010) used a split Bregman iteration (Goldstein and Osher, 2009) to solve a seismic tomography problem, imposing sparsity via soft thresholding (Donoho, 1995).…”
Section: Wavelets and Sparsity In Inverse Problemsmentioning
confidence: 99%
“…Most of these inverse problems have been in the estimation of log-transformed permeability fields (Li and Jafarpour, 2010;Jafarpour, 2013), seismic tomography (Loris et al, 2007;Simons et al, 2011;Gholami and Siahkoohi, 2010) and estimation of point and distributed emissions (Hirst et al, 2013;Martinez-Camara et al, 2013). A more detailed review of the sparse reconstruction methods can be found in our previous paper .…”
Section: Introductionmentioning
confidence: 99%